"That is Why I am Telling this Story": Musical Analysis as Insight into the Transmission of Knowledge and Performance Practice of a Wapurtarli Song by Warlpiri Women from Yuendumu, Central Australia. (December 2021) - CURRAN, GEORGIA; YEOH, CALISTA
Abstract: Insights into the knowledge, performance, and transmission of songs are pivotal in ensuring the survival of traditional Aboriginal songs. We present the first in-depth musical analysis of a Wapurtarli yawulyu song set sung by Warlpiri women from Yuendumu, Central Australia, recorded in December 2006 with a solo lead singer accompanied by a small group. Our musical analysis reveals that there are various interlocking parts of a song, and this can make it difficult for current generations to learn songs. The context of musical endangerment and the musical analyses presented in our study show that contemporary spaces for learning yawulyu must consider the complex components that come together for a song set to be properly performed.